1976
DOI: 10.1063/1.322870
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine metal particles

Abstract: In this paper we present a novel and versatile technique for the production of ultrafine metal particles by evaporation from a temperature-regulated oven containing a reduced atmosphere of an inert gas. An extensive investigation of particles of oxidized AI, with diameters of 3 to 6 nm, has been performed. We have also studied ultrafine particles of Mg, Zn, and Sn produced in the same manner. A supplementing investigation has been carried out for particles of Cr, Fe, Co, Ni, Cu, and Ga, as well as larger Al pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
598
4
21

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,633 publications
(652 citation statements)
references
References 120 publications
29
598
4
21
Order By: Relevance
“…15,16 Gum arabic is generally accepted to be a mixture of salts of calcium, magnesium, and potassium formed by the union of these elements with gummic acid. The gum is chiefly composed of calcium arabate.…”
Section: A Particle Preparationmentioning
confidence: 99%
“…15,16 Gum arabic is generally accepted to be a mixture of salts of calcium, magnesium, and potassium formed by the union of these elements with gummic acid. The gum is chiefly composed of calcium arabate.…”
Section: A Particle Preparationmentioning
confidence: 99%
“…The classical technique of gas evaporation was introduced in 1976 4 and has become a leading method for production of high-quality nanoparticles. [5][6][7] In the original advanced gas deposition arrangement, the source metal is heated up beyond the melting point, in an ambient of inert gas, and the source metal evaporates.…”
Section: Sample Preparation and Descriptionmentioning
confidence: 99%
“…Statistical analysis indicated that the size of the particles fit a log-normal distribution with a median diameter d g of 4.22 nm and a standard deviation ln g of 0.26. The diameter of average volume, d v , obtained from the expression d v =exp(lnd g +1.5ln 2  g ) (Granqvist & Buhrman, 1976), was 4.67 nm. The solgel systems were synthesized by a similar method to that used to prepare self-formed CoFe 2 O 4 ionic ferrofluids (Li et al, 2007), whereby the ferrofluid is formed through self-ionization of the nanoparticles and letting the metal ions absorb on the remaining part of the particles to prevent aggregation by electrostatic repulsive force.…”
Section: Methodsmentioning
confidence: 99%